How can the Learning Spirit of Buddhist Sunday School Students be enhanced through the Gamification Method? - Ingga Anjani; Vike Aprilianin Marwintaria Saputri; Ayu Andriyaningsih; Sutiyono Sutiyono; Susanto Susanto; Rina Manggalani; Tejo Ismoyo (Universitas Sebelas Maret, 2024)
This study aimed to find the effect of gamification methods on the enthusiasm of Buddhist Sunday School students to learn. The problems that occur are challenges for Buddhist Sunday School teachers in class management such as human resources, facilities and infrastructure and implementation of learning, low enthusiasm for learning of Buddhist Sunday School students, limitations in using learning methods, some students were seen chatting during the worship service, many pre-kindergarten students played during the worship service, and some children arrived late to Buddhist Sunday School. This study used a quantitative research approach by providing questionnaires to respondents. The subjects of this study are 30 people, obtained by a total sampling technique, namely using the entire population as respondents. The study results showed a significant favorable influence between the gamification method and students' enthusiasm for learning. The study result states that the gamification method affects learning enthusiasm by 52.1%, and other factors influence the remaining value of 47.9%. This study has practical implications in education; gamification can be considered in the learning process, such as using points, levels, or challenges to motivate students and make learning more enjoyable.